PEMODELAN SISTEM INFORMASI PROYEK AKHIR POLITEKNIK JAMBI - Akhmad Faisal Husni (Jurnal Ilmiah Matrik, 2016)
Final Project is a compulsory subject to be resolved as a condition of graduation Politekni Jambi in academics. Administrative management of the final project at the Politeknik Jambi still considered less than optimal in terms of time. This information system modeling can be improved continuously over time can develop in a sustainable and thus can help improve the terms of service for the Politeknik Jambi. The final goal of this research, generating an information system modeling the final project is used as a reference in building information systems that include project activities end environment Politeknik Jambi, to assist existing problems, in accordance with the standards set.